Identification and classification of the key competencies for social project managers in Agadir, Morocco - Habiba, Abou-hafs. (Archives of Business Research, 2019)
The question of project manager competencies and especially in social projects is very important to study to minimize the project fail. The researchers’ work shows the relationship that may exist between project manager competencies and project success. It is well understood that technical competencies have a significant effect on project success, but there are also behavioral competencies which are more important. The present study tries to show that combine behavioral (soft) skills and technical (hard) skills are important to be a good social project manager. The purpose of this paper is to show, on the basis of a quantitative study carried out among 120 managers of social projects in cooperatives located in the city of Agadir (Morocco), that project manager competency are categorized in behavioral skills and technical skills. The result of this study shows that the category of behavioral competencies is more important to achieve success. Consequently, the six-first key competencies identified are commitment and trust, discipline, patience, transparency, good communication, good coordination and work involvement.